Penggandaan separa dalam dialek Perak: suatu analisis autosegmental (Jurnal Bahasa, 2005)
Reduplication is a process of root receives an affixation. In reduplica-tion, the affixation is represented in a form of CV element (non-seg-ment fonem) the so called a template of reduplication. Based on seg-mental phonology, this tamplate must be given segmental content by linking its elements to the available root melody (fonem). The template of the partial reduplication in the Perak dialect (PD) is a CVC . The first C is a slot for an initial consonant of a root and the second C is a slot for a consonant off nal position of a root. Mean-while, the segmen V is a slot for a specific schwa vowel which is defaultly inserted. In the case of root containing consonant final posi-tion, the assimilation and the /lc/ glotalisation processes will occur after the process of specific schwa insertion has been dealt with.